2004
DOI: 10.1007/s11664-004-0203-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the electrical properties and the interfacial microstructures of TiAl-based ohmic contacts to p-type 4H-SiC

Abstract: In order to understand a mechanism of TiAl-based ohmic contact formation for p-type 4H-SiC, the electrical properties and microstructures of Ti/Al and Ni/Ti/Al contacts, which provided the specific contact resistances of approximately 2 ϫ 10 Ϫ5 Ω-cm 2 and 7 ϫ 10 Ϫ5 Ω-cm 2 after annealing at 1000°C and 800°C, respectively, were investigated using x-ray diffraction (XRD) and highresolution transmission electron microscopy (HRTEM). Ternary Ti 3 SiC 2 carbide layers were observed to grow on the SiC surfaces in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 31 publications
4
58
0
Order By: Relevance
“…For MAX phases, the most well-known example of the first category of reactions is Ti 3 SiC 2 which is often found at the interface when Ti and SiC are in contact at higher temperatures, e.g., when Ti is used as braze material to bond SiC to SiC or in Ti-reinforced SiC metal matrix composites [3]. The most relevant example as a thin-film synthesis method is Ti 3 SiC 2 synthesized by annealing of Ti-based contacts used as electrodes in SiC-based semiconductor devices [191,192,193,194]. Another example relevant to the semiconductor industry is Ti 2 GaN which can form at the interface between Ti-based films on GaN substrates [195].…”
Section: Solid-state Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For MAX phases, the most well-known example of the first category of reactions is Ti 3 SiC 2 which is often found at the interface when Ti and SiC are in contact at higher temperatures, e.g., when Ti is used as braze material to bond SiC to SiC or in Ti-reinforced SiC metal matrix composites [3]. The most relevant example as a thin-film synthesis method is Ti 3 SiC 2 synthesized by annealing of Ti-based contacts used as electrodes in SiC-based semiconductor devices [191,192,193,194]. Another example relevant to the semiconductor industry is Ti 2 GaN which can form at the interface between Ti-based films on GaN substrates [195].…”
Section: Solid-state Reactionsmentioning
confidence: 99%
“…MAX phases synthesized by solid state reactions or sputter deposition can potentially be used as electrodes in SiC-, AlN-, or GaN-based semiconductor devices or sensor applications [195,198,326]. "Ti-based" contacts to SiC are in use and typically contain Ti 3 SiC 2 formed by solid state reactions [191,192,326]. A more exotic suggestion is the claim (based on theoretical calculations of the dielectric function and infrared emittance [327,328]) that Ti 4 AlN 3 and V 4 AlC 3 have the potential to be used as a coating on spacecrafts to avoid solar heating and also increase the radiative cooling in future space missions to Mercury.…”
Section: Applicationsmentioning
confidence: 99%
“…Thus, a current transport mechanism between metal/implanted SiC interface is not clearly understood. In our previous paper [8], we reported that the lower r c values of the p-type 4H-SiC layers using Ti/Al and Ni/Ti/Al contacts were due to the formation of Ti 3 SiC 2 layers at the interfaces between the as-deposited Ti/Al or Ni/Ti/Al metals and p-type 4H-SiC layers.…”
Section: Introductionmentioning
confidence: 89%
“…Tanimoto et al examined the microstructure at the interface between TiAl contacts and the SiC using Auger electron spectroscopy and found that carbides containing Ti and Si were formed at interface (Tanimoto et al, 2002). Recently, transmission electron microscopy (TEM) studies by Tsukimoto et al have provided useful information in this aspect due to possible high-resolution imaging (Tsukimoto et al, 2004). They have found that the majority of compounds generated on the surface of 4H-SiC substrate after annealing consist of a newly formed compound and hence proposed that the new interface is responsible for the lowering of Schottky barrier in the TiAl-based contact system.…”
Section: Introductionmentioning
confidence: 99%